Advanced Driver Assistant System - S., Sanjay; S., Vasantha Kumar; Z., Mohamed Rifayee Hussain; K., Saravana Kumar; S., Dineshkumar; P. D., Rathika (Indian Journal of Computer Science, 2021)
Road accidents are the most terrifying thing that can happen to a driver. Worst of all, we refuse to learn from our mistakes along the way. The majority of road users are aware of the general rules and safety measures to take while on the road but injuries and crashes are caused by the negligence of road users. The most common cause of accidents and collision is human error. The aim of this project is to automate and improve the safety of vehicles. Lane Departure Warning System (LDWS) and Emergency Driver Assist System (EDAS) are described in this paper. The LDWS uses camera to track lane markers to see if the driver is drifting accidentally. In this project, whenever the vehicle is moving out of the lane, the device gives the driver a warning in the form of audio or visual signal. Whenever the driver’s attention deviates from driving activity for a particular interval of time, EDAS alerts the driver.